2009
DOI: 10.1074/jbc.m807670200
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Regulatory Role for the mSin3A-HDAC Complex in Pluripotency through Nanog and Sox2

Abstract: Large networks of proteins govern embryonic stem (ES) cell pluripotency. Recent analysis of the critical pluripotency factors Oct4 and Nanog has identified their interaction with multiple transcriptional repression complexes, including members of the mSin3A-HDAC complex, suggesting that these factors could be involved in the regulation of Oct4/Nanog function. mSin3A is critical for embryonic development, but the mechanism by which the mSin3A-HDAC complex is able to regulate ES cell pluripotency is undefined. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 33 publications
(31 reference statements)
9
56
1
2
Order By: Relevance
“…2A). These results agreed with pre-http://bmbreports.org BMB reports (8,11). Recently, it was reported that a repressor complex including mSin3A, HDAC1, and HDAC2 is involved in ES cell maintenance (11).…”
Section: Differentiation Of Mouse Es Cells Induced By a Subset Of Hdasupporting
confidence: 82%
“…2A). These results agreed with pre-http://bmbreports.org BMB reports (8,11). Recently, it was reported that a repressor complex including mSin3A, HDAC1, and HDAC2 is involved in ES cell maintenance (11).…”
Section: Differentiation Of Mouse Es Cells Induced By a Subset Of Hdasupporting
confidence: 82%
“…Hdac1, Hdac2 and Sin3a were found in complex with Nanog, Sox2 and Oct4 in a transcription regulatory complex known as Nanog and Oct4 associated deacetylase (NODE), which regulated Nanog expression. [31][32][33] In line with this it was shown that HDAC inhibitors can enhance the formation of induced pluripotent stem cells, probably by derepression of critical pluripotency regulators, including Nanog, Oct4 and Klf4. 34 Alternatively, since Hdac1 was found at predominantly active genes in embryonic stem cells and early thymocytes it is also possible that Hdac1 is required for activation of regulators of self-renewal.…”
Section: Discussionmentioning
confidence: 80%
“…Deletion of LSD1 perturbs the CoREST complex but does not affect Oct4 expression (39), whereas loss of MBD3 (central component of NuRD) prevents Oct4 from being repressed at all, even under differentiating conditions (40). By process of elimination, this suggests that the Sin3A complex may positively regulate Oct4 and Nanog expression; and indeed Baltus et al (41) were able to demonstrate a direct role for the Sin3A/HDAC complex in the activation of the Nanog promoter. More recently, a genome-wide promoter analysis in ES cells revealed that HDAC1 binds close to the transcriptional start site of many pluripotent factors, including Oct4, Nanog, Sox2, and Rex1 (7), again suggesting a positive role in the maintenance of cell self-renewal.…”
Section: Hdac1/2 Regulate the Expression Of Core Pluripotency Factorsmentioning
confidence: 94%